High revision rates following repeat septic revision after failed one-stage exchange for periprosthetic joint infection in total knee arthroplasty. (1st March 2022) - Neufeld, Michael E.; Liechti, Emanuel F.; Soto, Fernando; Linke, Philip; Busch, Sophia-Marlene; Gehrke, Thorsten; Citak, Mustafa
Abstract : Aims: The outcome of repeat septic revision after a failed one-stage exchange for periprosthetic joint infection (PJI) in total knee arthroplasty (TKA) remains unknown. The aim of this study was to report the infection-free and all-cause revision-free survival of repeat septic revision after a failed one-stage exchange, and to determine whether the Musculoskeletal Infection Society (MSIS) stage is associated with subsequent infection-related failure. Methods: We retrospectively reviewed all repeat septic revision TKAs which were undertaken after a failed one-stage exchange between 2004 and 2017. A total of 33 repeat septic revisions (29 one-stage and four two-stage) met the inclusion criteria. The mean follow-up from repeat septic revision was 68.2 months (8.0 months to 16.1 years). The proportion of patients who had a subsequent infection-related failure and all-cause revision was reported and Kaplan-Meier survival for these endpoints was determined. Patients were categorized according to the MSIS staging system, and the association with subsequent infection was analyzed. Results: At the most recent follow-up, 17 repeat septic revisions (52%) had a subsequent infection-related failure and the five-year infection-free survival was 59% (95% confidence interval (CI) 39 to 74). A total of 19 underwent a subsequent all-cause revision (58%) and the five-year all-cause revision-free survival was 47% (95% CI 28 to 64). The most common indication for the first subsequent aseptic revision was loosening. The MSIS stage of the host status (p = 0.663) and limb status (p = 1.000) were not significantly associated with subsequent infection-related failure. Conclusion: Repeat septic revision after a failed one-stage exchange TKA for PJI is associated with a high rate of subsequent infection-related failure and all-cause revision. Patients should be counselled appropriately to manage expectations. The host and limb status according to the MSIS staging system were not associated with subsequent infection-related failure. Cite this article: Bone Joint J 2022;104-B(3):386–393.